INFLUENCER CULT AND INFORMATION SYSTEM ECOSYSTEM: FROM CULTURAL CONSUMPTION TO DIGITAL IDOLATRY IN THE PERSPECTIVE OF NEW CULTURE AND QUR'ANIC VALUES - Achyar Zein; Mailin Mailin (Program Pascasarjana UIN Sumatera Utara, 2025)
This study explores the phenomenon of digital idolatry as a cultural manifestation within the algorithmic ecosystem of social media. Using a mixed-methods approach, the research integrates quantitative analysis through Structural Equation Modeling-Partial Least Square (SEM-PLS) and qualitative interpretation based on thematic interviews. The quantitative results reveal that cultural consumption and information system quality significantly influence digital idolatry, while information quality has a weak impact. These findings indicate that technological reliability and cultural participation are more decisive in shaping excessive attachment to digital figures than informational clarity alone. The qualitative findings reinforce this pattern, highlighting emotional attachment, lifestyle imitation, ritualized online behavior, and financial sacrifice as expressions of collective worship in digital spaces. Interpreted through Qur'anic values, such as wasathiyyah (moderation), tabayyun (verification), and anti-israf (avoidance of excess), the study argues that digital idolatry reflects a moral imbalance fostered by algorithmic design and social validation systems. The research contributes to the integration of socio-technical theory with ethical theology, offering a normative framework for promoting critical, balanced, and ethical digital engagement. This study emphasizes the urgency of developing spiritual digital literacy as a cultural counterweight in the age of algorithmic influence.